2019
DOI: 10.1007/s00605-019-01341-2
|View full text |Cite
|
Sign up to set email alerts
|

Li–Yorke chaos for composition operators on $$L^p$$-spaces

Abstract: Li-Yorke chaos is a popular and well-studied notion of chaos. Several simple and useful characterizations of this notion of chaos in the setting of linear dynamics were obtained recently. In this note we show that even simpler and more useful characterizations of Li-Yorke chaos can be given in the special setting of composition operators on L p spaces. As a consequence we obtain a simple characterization of weighted shifts which are Li-Yorke chaotic. We give numerous examples to show that our results are sharp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Chaotic operators are well studied in linear dynamics and well understood. For example, in [8], the authors showed a characterization of Li-Yorke chaos for bilateral weighted backward shifts. Moreover, Grosse-Erdmann in [14] gave a complete characterization of backward weighted shifts which are chaotic.…”
Section: Types Of Chaosmentioning
confidence: 99%
See 2 more Smart Citations
“…Chaotic operators are well studied in linear dynamics and well understood. For example, in [8], the authors showed a characterization of Li-Yorke chaos for bilateral weighted backward shifts. Moreover, Grosse-Erdmann in [14] gave a complete characterization of backward weighted shifts which are chaotic.…”
Section: Types Of Chaosmentioning
confidence: 99%
“…A systematic study of composition operators on L p (X) in the setting of linear dynamics was initiated in [2] and [8]. The motivation for the study of composition operators is to have a concrete but large class of operators which can be utilized as examples and counterexamples in linear dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a general setting, hypercyclic composition operators and topologically mixing composition operators on L p -spaces were completely characterized in a joint work of the authors with Bayart in [2]. Li-Yorke chaotic composition operators on L p -spaces were completely characterized in a joint work of the authors with Bernardes Jr. in [6]. Recently, generalized hyperbolicity among composition operators was characterized by the first author, D'Aniello and Maiuriello in [10].…”
Section: Introductionmentioning
confidence: 99%
“…At this point we like to point out that a systematic study of composition operators in the setting of linear dynamics was initiated in [3] and [6]. In [3], necessary and sufficient conditions were given for a composition operator to be topologically transitive and mixing.…”
Section: Introductionmentioning
confidence: 99%